Cultivating Creativity in Buddhist Students through Buddhayana-Based Learning Methods - sonia, Sonia; Sutawan, Komang; Dharmatanna, Sandjaja; Nyanabhadra, Phap Tu (LPPM STIAB JINARAKKHITA LAMPUNG, 2024)
This study aims to examine the effect of Buddhayana-based learning methods on student creativity. Buddhayana-based learning methods focus on integrating Buddhist teachings in the teaching and learning process, emphasizing moral and ethical principles that influence individual behavior in daily life. Buddhayana, which is part of the Great Sangha of Indonesia, seeks to integrate various Buddhist traditions into a harmonious whole and spread Buddhism inclusively. Creativity is defined in this study as the ability to generate new ideas or solutions in solving problems and see new relationships between existing concepts. This study used a quantitative approach with a survey method. The population in this study amounted to 199 students, with a sample of 64 students selected using the Proportional Random Sampling technique. The results showed a significant positive influence between Buddhayana-based learning methods on student creativity. The analysis shows a strong relationship, with the method influencing most of the variation in student creativity, while a small part is influenced by other factors.